42=7x+7(-2x+18)

Simple and best practice solution for 42=7x+7(-2x+18) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 42=7x+7(-2x+18) equation:


Simplifying
42 = 7x + 7(-2x + 18)

Reorder the terms:
42 = 7x + 7(18 + -2x)
42 = 7x + (18 * 7 + -2x * 7)
42 = 7x + (126 + -14x)

Reorder the terms:
42 = 126 + 7x + -14x

Combine like terms: 7x + -14x = -7x
42 = 126 + -7x

Solving
42 = 126 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
42 + 7x = 126 + -7x + 7x

Combine like terms: -7x + 7x = 0
42 + 7x = 126 + 0
42 + 7x = 126

Add '-42' to each side of the equation.
42 + -42 + 7x = 126 + -42

Combine like terms: 42 + -42 = 0
0 + 7x = 126 + -42
7x = 126 + -42

Combine like terms: 126 + -42 = 84
7x = 84

Divide each side by '7'.
x = 12

Simplifying
x = 12

See similar equations:

| 11x-23y=-5 | | (1/36)-(1/40)=(1/x) | | 4/9*7/9 | | 4/9/7/9 | | 20x^2-40x-52=0 | | 4m-12=2m-9 | | (1/36)-(1/40)=(1/t) | | (9y-8)(y+5)=(ny-2) | | 6+3x+4x= | | 4(3y-4.7)+17.4=7(4y-0.2) | | c=0.17w+0.63 | | (2x-3)+(x+5)=90 | | -4+2x=x+3 | | (2x^2+15x+21)/(x+5) | | -8(5-n)=-104 | | 8y=64.72 | | 81x^2+kx+25=0 | | 1x+3y=360 | | 6(x+4)=2x+60 | | 2x^2+9x-8=0 | | 4=8/12(-8)+b | | 2x+3x+15=20 | | -3x^2-237=0 | | M/4+4=17 | | (8m-4)/(2m-1) | | 1m+6.74+.7m=-3.8 | | -3x^2=-237 | | 3x^4-12x^3=0 | | 5d+9ford=104 | | 2(3x-5)+14=4(x+9)+4 | | 603+0.5m=16.3 | | 3.14*4*5*5= |

Equations solver categories